Navigating the intersection of international politics and international education: A historical and contemporary analysis - Gultekin, Osman (Journal of International Students, 2025)
International education and the process of internationalization have evolved through distinct historical phases, each characterized by shifting global political outlooks and increasing complexity. International politics and the global power hierarchy have always played a significant role in shaping the development of international education and directions of academic mobility. Since the era of ancient Greece, various periods have witnessed diverse patterns of student mobility concentrated in specific geographic regions, paralleling prevailing power structures. Currently, international education is undergoing a distinct phase in which its significance in public diplomacy and foreign policy is widely recognized. However, its use for further national interests has also been criticized for potential manipulation. This article provides a historical background and conceptual framework for understanding the intersection of international politics and international education.